Lithium promotion of Pt/m-ZrO2 catalysts for low temperature water-gas shift. (22nd August 2022) - Rajabi, Zahra; Martinelli, Michela; Watson, Caleb D.; Cronauer, Donald C.; Jeremy Kropf, A.; Jacobs, Gary
Abstract: Low temperature water-gas shift (LTS) is an important reaction occurring in a fuel processor for producing and purifying hydrogen. Platinum supported on m-ZrO2 belongs to a family of catalysts consisting of metal nanoparticles and an active partially reducible oxide, with the catalysis proposed to occur at the boundary between metal particles and the support. In this investigation, increasing the loading of lithium dopant increased the LTS rate up to 0.54 wt % lithium, where conversion was 2.4 times that of the unpromoted catalyst at 260 °C. Further increases in lithium loading up to 1.5 wt % decreased the rate, although it remained higher than that of the unpromoted catalyst. Infrared spectroscopy and CO2 temperature programmed desorption experiments showed three effects with increasing lithium loading: (1) lithium promoter weakened the C –H bond of formate, the proposed rate limiting step of the interfacial surface formate mechanism; (2) high levels of lithium suppressed the platinum site capacity required for hydrogen transfer; and (3) high levels of lithium increased catalyst basicity. Aspects (2) and (3) tended to inhibit desorption of product CO2, an acidic molecule the removal of which is metal-catalyzed. XANES and XPS experiments revealed that electron transfer to enrich Pt nanoparticles is unlikely the root cause of C –H bond weakening in formate. However, other electronic effects (e.g., electrostatic effects or molecular rearrangement due to enhanced basicity) were not ruled out. Highlights: A dopant level of 0.54% lithium was optimal for promoting 2%Pt/m-ZrO2 for water-gas shift. At the optimum Li loading, the CO conversion was 2.4 times that of the unpromoted catalyst. DRIFTS of adsorbed CO showed that increasing Li loading improves formate C –H bond weakening. Excessive loadings of Li above 0.75%Li increase catalyst basicity so that CO2 desorption is impeded. Excessive loadings of Li above 0.75%Li block Pt sites needed for H-transfer and CO2 desorption.